Thermal, optical and electrical properties of UV-curing screen-printed glass substrates - ARMAN KANDIRMAZ, EMİNE; BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (SPRINGER, 2019)
In this study, the hydroxyl functionality of the polyaniline surface was obtained using hydroxyethyl methacrylate and acrylated with isocyanatoethyl methacrylate. Coating formulation being curable with UV was designed by mixture of acrylated PANI (a-PANI) (0-5wt%), polyethylene glycol diacrylate, trimethylolpropane triacrylate, hydrolyzed 3-(methacryloxy) propyl trimethoxysilane (hydMEMO) and photoinitiator. The hybrid composite formulation has been printed on the glass surface with the method of screen printing. The chemical structure and the properties of thermal, electrical and surface obtained products were determined with ATR-FTIR, goniometer, current-voltage meter, scanning electron microscopy (SEM) and thermogravimetric analysis. ATR-FTIR results have shown that all materials were clearly produced. SEM results have revealed that PANI was dispersed at the composite in a stable manner. The conductivity value of the conductive line printed with F5a-PANI was found to be 3.7x10(-3)S. The best electrical results have presented that PANI has been beneficial for conductive line, and thus, screen printing was a convenient method for printing conductive lines.
Keywords: Conductive polymer; PANI; Screen printing; UV curing; Surface modification; CONDUCTING POLYMERS; COMPOSITE; PERFORMANCE; SENSOR